UTILIZING BIM AND SIMULATION TO DOCUMENT THE HERITAGE BUILDINGS' SPACE QUALITY, CASE STUDY BLENDUK CHURCH - Michelle Faustine Gunawan (Journal of Architecture & Environment, 2026)
Indonesia has a lot of heritage buildings that are either damaged or facing design changes. Those damage and design changes transformed the original spatial quality inside the building and erased a part of the history. Simulation methods have the potential to replicate the lost spatial quality and comfort. Therefore, this study aims to test the potential of utilizing BIM and simulation software in digital conservation with Blenduk Church in Semarang as the case study. The data was collected through direct field measurement to obtain the dimension and daylight intensity of Blenduk Church. The data was used to create 3D models of Blenduk Church, the old design and the current design, utilizing Rhino and Autodesk Revit. The 3D models are simulated with DiaLUX to find the daylight intensity and the microclimate surrounding the building. The data validation process includes comparing both data that was obtained through direct measurement and simulation, then calculated the standard deviation. By doing the data validation, it was found out that the standard deviation is 2,8%, which indicates that the simulation software is relevant to be utilized as a tool for digital revitalization as the deviation is still within the acceptable tolerance limits. This research demonstrates that CAD, BIM, and architectural simulation technologies can be used to document the space quality of heritage buildings that have been altered or demolished. This research could contribute as a blueprint to digital conservation that is not limited to recreating 3D model, but also continuous research of the missing space qualities.